Analisis Peran Home Industry Dalam Meningkatkan Perekonomian Masyarakat (Studi Pada Win Mebel Bondansari, Kecamatan Wiradesa Kabupaten Pekalongan) - Nivia Audria Mina; Anastasya Putri; Muhammad Fauzan; Hendri Hermawan Adi Nugraha (Robust: Research of Business and Economics Studies, 2022)
This study aims to determine the effect of the home furniture industry in improving the economy of the community in Bondansari village. Bondansari is one of the villages in the District of Wiradesa and is close to the District of Siwalan. With a wide expanse of rice fields, the livelihood of the population is not only as farmers, but there are also several home industry entrepreneurs in various types of businesses. In Bondansari Village there is a home industry, namely Win Furniture. This research was conducted using qualitative research methods with supporting data from previous research journals that are relevant to this research. The results of this study indicate a positive impact from the Win Furniture home industry in an effort to improve the economy of the community in Bondansari village. Besides the positive impact, there are obstacles that hinder the development of the home industry win furniture. Lack of capital, lack of equipment, and erratic orders, so that sometimes there is a shortage of manpower for the time promised. The strategy that needs to be done is by building relationships so that they are able to develop their business well and